Analisis Pendapatan Petani yang menggunakan Pupuk Bersubsidi pada Usahatani Padi Sawah di Desa Padangguni Kecamatan Padangguni Kabupaten Konawe - Ahmad Riky Ramdani; Suharjo Suharjo; I Made Sukratman (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
The purpose of the study was to determine the level of income of rice farming businesses managed by farmers in Padangguni Village, Padangguni District, Konawe Regency. This research will be conducted in Padangguni Village, Padangguni District, Konawe Regency. In this study, a sample of 15% of the population was taken to be used as a sample. The population in this study was 275 farmers so that the sample taken was 34 rice farmers. The data analysis used was Income Analysis. Rice farmers received an average income of IDR 25,183,298 / Ha. The average farming costs incurred by farmers were IDR 8,080,544 / Ha. Therefore, the average income obtained by rice farmers was IDR 17,102,754 / Ha. So that the average seasonal income is Rp. 25,183,298/Ha and the total farming costs incurred in one season are Rp. 8,080,544/Ha and the results obtained are an average of Rp. 17,102,754/Ha. This means that TR > TC, which means that the business is profitable.